2020
DOI: 10.1055/s-0040-1718508
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da reprodutibilidade das classificações Lauge-Hansen, Danis-Weber e AO para fraturas do tornozelo

Abstract: Resumo Objetivo Avaliar a reprodutibilidade intra- e interobservador das classificações de Lauge-Hansen, Danis-Weber e Arbeitsgemeinschaft für Osteosynthesefragen (AO) para as fraturas de tornozelo, e a influência do estágio de formação dos participantes na avaliação. Métodos Foram selecionadas radiografias de 30 pacientes com fratura de tornozelo nas incidências anteroposterior (AP), perfil e AP verdadeiro. Todas as imagens foram avaliadas por 11 participantes em diferentes estágios de for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…Moreover, the explanation made by the authors prior to the evaluation by the participants may have left doubts about the correct application of the system, a fact that may justify the greater agreement among residents who used illustrative figures more often. Corroborating our hypothesis, Sacramento et al 20 studied patients with ankle fracture, demonstrating that residents had greater inter- and intraobserver agreement for the classifications of Danis-Weber, Lauge-Hansen and group A.O. (Arbeitsgemeinschaft für Osteosynthesefragen), suggesting that less experienced observers probably used more of the images of the classifications available as feedback.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Moreover, the explanation made by the authors prior to the evaluation by the participants may have left doubts about the correct application of the system, a fact that may justify the greater agreement among residents who used illustrative figures more often. Corroborating our hypothesis, Sacramento et al 20 studied patients with ankle fracture, demonstrating that residents had greater inter- and intraobserver agreement for the classifications of Danis-Weber, Lauge-Hansen and group A.O. (Arbeitsgemeinschaft für Osteosynthesefragen), suggesting that less experienced observers probably used more of the images of the classifications available as feedback.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have observed that more complex systems for the classification of fractures present lower interobserver agreement due to the greater number of options for the evaluators. 20,21 We observed greater agreement in the most complex cases, involving the four anatomical areas of the tibial plateau, as well as in less complex fractures, involving a single area. However, due to the limited sample size of the present study, this information should be considered with restrictions.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Lauge-Hansen described a classification of ankle fractures that depends on foot position yielding a rotational or translational low energy ankle fractures. 1 It showed great reproducibility and interobserver agreement in a recent report. 2 While others found some downsides of its use, the classification's most important attribute is that it helps recognizing the mechanism of injury and associated nonosseus injuries that cannot be seen on plain films.…”
Section: Introductionmentioning
confidence: 81%